Gesture Language Recognition Through ‎Computer Vision and a Spatial-Temporal ‎Mathematical Model - Manikandan , S.; Suma , T.; Dhanalakshmi, P.; Rajheshwari , K. C.; Tamilselvi , T.; Subedha , V. (International Journal of Basic and Applied Sciences, 2025)
For people with speech and hearing impairments, sign language is a vital form of communication that allows them to communicate and en-‎gage with others. Nonetheless, a major obstacle is the general public’s limited comprehension of sign language. For the deaf and mute com-‎communities, this communication gap frequently results in challenges with social inclusion, education, and career prospects. To solve ‎this problem, researchers are increasingly using deep learning and artificial intelligence (AI) techniques to create automatic sign language ‎recognition (SLR) systems that can instantly translate sign motions into speech or text. This paper presents a hybrid method that combines ‎continuous sign language recognition (CSLR) and isolated sign language recognition (SLR) into a single deep learning framework. The ‎system uses a Spatial-Temporal Network (STNet) to identify dynamic sign sequences in CSLR and a Convolutional Neural Network ‎‎(CNN) for isolated sign identification. An ensemble learning technique is included to increase model robustness, and an optimized Inception-based architecture is utilized for isolated sign classification to boost performance. Additionally, a novel Spatial Resonance Module ‎‎(SRM) refines frame-to-frame feature extraction, and a Multi-Temporal Perception Module (MTPM) strengthens long-range dependency ‎recognition in sign sequences. These advancements contribute to higher accuracy and efficiency in sign language interpretation. Experimental validation of the proposed system was conducted using benchmark datasets, demonstrating superior performance compared to existing state-of-the-art techniques. The model achieved an accuracy of 98.46% in isolated sign recognition and exhibited a 2.9% improvement in ‎CSLR tasks. The ability to accurately recognize and translate sign language in both isolated and continuous contexts makes this system ‎highly suitable for real-time applications, including assistive communication devices, virtual interpreters, and educational tools. The pro-‎posed research has the potential to significantly impact accessibility and inclusivity for individuals with speech and hearing impairments. By ‎integrating deep learning with real-time processing, this system enhances human-computer interaction and fosters seamless communication ‎between sign language users and the broader community. Future research can explore the integration of additional modalities, such as facial ‎expressions and hand movement trajectories, to further refine sign language recognition models and ensure even greater accuracy and adapt-‎ability.